Beyond public policy : a public action languages approach - Spink, Peter Kevin (New horizons in public policy, 2019)
Public policy is an expression that has come to dominate the way people talk about doing government and public administration and is seen as a central component of the modern democratic order. Adopting an innovative 'public action languages' approach, Beyond Public Policy shows how policy is only one of many powerful social languages (budgeting, planning, rights, directives and protests, amongst others) used to make things happen in the ever-changing arena of public affairs; where they may cooperate, compete, or just go their own way. Opening up discussions on the varied ways that people talk about and act in relation to the public good, this is a fascinating insight into the multiplicity of social languages used to negotiate possibilities in public affairs. Social languages are examined as being performative parts of everyday life, and examples from different places and times are used to illustrate the importance of these language forms. Political science, public administration, social psychology and sociology scholars will find this book a vital reference with its advanced approach to public affairs. Professionals in NGOs, public service and government, as well as activists will also greatly benefit from the practical advice and real-life case studies the book offers.